Analysis of Teaching Reform in International Trade Practice Courses - Fan, Pengzhen (Journal of Education and Educational Technologies, 2023)
With the arrival of the "Internet plus" era and the implementation of the "the Belt and Road" policy, the demand for innovative and compound high-quality talents in the field of international trade is increasing, so the course of international trade practice should also keep pace with the times. This article is based on the cultivation goal of applied talents and proposes curriculum reform suggestions that are in line with the new era, in response to the shortcomings in traditional teaching of international trade practice. With the proposal of the "the Belt and Road" policy, enterprises have more and more demands for international trade talents, but the international trade talents trained by most schools can not meet the requirements of enterprises. As one of the core courses of international economy and trade, international trade practice has a strong timeliness and practicality, and the traditional curriculum model can no longer fully meet the needs of the society for international trade talents. Therefore, The task of reforming the teaching of international trade practice courses to keep up with the times is urgent. In just a few months, the construction of “Ding zhen" symbol and the creation of a mimetic environment of "Litang culture" have enabled this small city in western Sichuan to realize the rapid improvement of commercial value. This paper analyzes the shaping and marketing process of “Ding zhen" symbol in the new media environment, and discusses how to realize the positive communication of the city from the phenomenon level of Internet celebrity effect, and realize the urban marketing plan from point to surface.